A point mutation in the human transporter associated with antigen processing (TAP2) alters the peptide transport specificity - Armandola, Elena A.; Momburg, Frank; Nijenhuis, Marga; Bulbuc, Nadja; Früh, Klaus; Hämmerling, Günter J. (European journal of immunology, 1996)
The heterodimeric transporter associated with antigen processing (TAP1/TAP2) translocates peptides from the cytosol into the endoplasmic reticulum where loading of major histocompatibility complex class I molecules takes place. TAP transporters from different species are known to exhibit distinct transport specificities with regard to the C-terminal amino acid (aa) of peptides. Thus, human TAP (hTAP), and rat TAP (rTAP) containing the rTAP2a allele are rather promiscuous, whereas mouse TAP (mTAP), and rTAP containing the rTAP2u allele are restrictive and select against peptides with C-terminal small polar/hydrophobic or positively charged aa. The structural basis for this selectivity is not clear. To assess the relative contribution of the TAP1 and TAP2 subunits to transport specificity, we have constructed and analyzed interspecies TAP hybrids and point mutants of hTAP2 expressed in Sf9 insect cells and in TAP-deficient T2 cells. Transport assays with 20 C-terminal variants of the peptide RYWA-NATRSX showed that: first, transport specificity with regard to C-terminal aa is mainly influenced by TAP2, but TAP1 can also contribute. Second, the selective transport of peptides with C-terminal positively charged aa is critically controlled by the amino-terminal region (1-361) on the TAP2 chain, while transport of peptides with C-terminal small polar/hydrophobic aa is determined by residues located within as well as outside the region 1-361. Third, a single point mutation in hTAP2 (374A → D) resulted in a drastic alteration of the transport pattern. These results indicate that both TAP1 and TAP2 contribute to efficient peptide transport and that single point mutations in hTAP2 are able to alter the peptide transport specificity. This opens the possibility that naturally occurring mutations in one of the hTAP subunits may alter epitope selection in vivo.